Factorise 4b² + 16b ⇒ 4b(b+4)
expand (a-1)(a-2) ⇒ a(a-2) - 1(a-2) ⇒ a² - 2a - 1a + 2 ⇒a² - 3a + 2
factorise x² + 8x + 7 ⇒(x + 1) (x + 7)
evaluate y⁶ / y² ⇒ y * y * y * y * y * y / y * y = y⁴
if x = -1 and y = 5, find z when z = x² + 2y² ;
z = -1² + 2(5²) ⇒ 1 + 2(25) ⇒1 + 50 = 51
Make x the subject: y = 4x - 3
y = 4x - 3
<u>+3 +3</u>
3 + y = 4x
<u>÷4 ÷4 </u>
(3+y)/4 = x
Answer:
2
Step-by-step explanation:
Solve. To do so, change the division sign into a multiplication sign, and flip the second fraction:
(2/3)/(1/3) = (2/3) x (3/1)
Multiply across:
(2 * 3)/(3 * 1) = (6)/(3)
Simplify:
6/3 = 2
2 is your answer.
~
Answer:
67
Step-by-step explanation:
Mean is the average
Add up all the values and divide by the numbers there are.
In this case, divide by 9.
Hey there!
1, 8.95*.4= 3.58 was take off. 8.95-3.58= 5.37
$5.37
2.<span>A change from 85 to 72 represents a negative change (decrease) of -15.294117647058824%</span>